2014
DOI: 10.1038/cddis.2013.549
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor mediates raloxifene-induced apoptosis in estrogen receptor-negative hepatoma and breast cancer cells

Abstract: Identification of new molecular targets for the treatment of breast cancer is an important clinical goal, especially for triple-negative breast cancer, which is refractory to existing targeted treatments. The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor known primarily as the mediator of dioxin toxicity. However, the AhR can also inhibit cellular proliferation in a ligand-dependent manner and act as a tumor suppressor in mice, and thus may be a potential anticancer target. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 55 publications
5
77
0
Order By: Relevance
“…Recent studies suggest that AhR expression is also upregulated in breast cancer (Li et al, 2014). Interestingly, the AhR ligand raloxifene was recently reported to inhibit the growth of a triple negative breast cancer cell line via an AhR-dependent mechanism (O'Donnell, et al, 2014). A similar positive therapeutic outcome was achieved with the AhR ligand omeprazole in a triple negative breast cancer cell line (Jin et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies suggest that AhR expression is also upregulated in breast cancer (Li et al, 2014). Interestingly, the AhR ligand raloxifene was recently reported to inhibit the growth of a triple negative breast cancer cell line via an AhR-dependent mechanism (O'Donnell, et al, 2014). A similar positive therapeutic outcome was achieved with the AhR ligand omeprazole in a triple negative breast cancer cell line (Jin et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…We have previously identified Tnf and c-fos activity as the means by which aryl hydrocarbon receptor activation by the flavonoid chrysin leads to apoptosis (39). Also, the aryl hydrocarbon receptor has been found to mediate raloxifene-induced apoptosis in triple-negative breast cancer cells and estrogen receptor-deficient hepatoma cells (43). These studies represent instances in which the apoptogenic cascades activated by the AHR have been further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Although no binding sites were detected by bioinfor matics analyses for the aryl hydrocarbon receptor (AhR) in the promoter region of the FA2H, at least up to 10 kilobases, Δ 9 -THC has been suggested as a potential ligand for AhR due to its ability to induce the expression of CYP1A1 that is also regulated by AhR-mediated signaling in a murine hepatoma cell line (Roth et al, 2011). Based on these findings, we examined the expression levels of AhR-regulated genes, such as CYP1A2, CYP2S1, and UDP-glucuronosyltransferase 1A6 48 h after the exposure of Δ 9 -THC to MDA-MB-231 cells expressing functional AhR (Tijet et al, 2006; Beischlag et al, 2008; O’Donnell et al, 2014); however, no observable stimulation was detected, implicating the possible requirement of PPARα, but not AhR, in the induction of CYP1A1 by Δ 9 -THC in MDA-MB-231 cells. Since previous studies demonstrated that Δ 9 -THC had no binding/activation efficacy toward PPARα (Sun et al, 2006, 2007), the action point(s) of Δ 9 -THC on the induction of FA2H and CYP1A1 remain to be determined.…”
Section: Discussionmentioning
confidence: 99%